WEB-BASED INVENTORY MANAGEMENT SYSTEM UTILIZING THE FIRST IN FIRST OUT (FIFO) METHOD: A CASE STUDY OF CV BERKAH FOAM FURNITURE - Dwi Setiawan; Amalia Nur Risa Purnamasari; Indra Ava Dianta (UNIVERSITAS STEKOM, 2023)
CV Berkah Foam Furniture is a store that offers a variety of furniture, including tables, chairs, mattresses, wardrobes, and various other furniture items. The monthly process of compiling purchase and sales reports is time-consuming due to the need to manually input data from physical books into Microsoft Office Excel. The recording of expenses and inventory entries is carried out post-transaction, leading to inaccuracies in the records. This research was conducted with the aim of developing an inventory management information system to assist administrators in generating sales and purchase reports. The chosen inventory method is the First In First Out (FIFO) method, and the system is designed using PHP and MySQL. The inventory management information system provides accurate and efficient information on inventory levels and reports tailored to the company's needs, minimizing inventory surplus and shortages by introducing a new system for data processing. The research methodology follows the Research and Development (R&D) approach, involving identifying potential issues, data collection, product design, design validation, product creation, product testing, and the development of the inventory management information system. Data collection methods include interviews, observations, and literature reviews. The system's testing yielded a score of 38 from internal validators and a score of 38 from external validators, while 10 respondents rated it 180 with a 90% satisfaction rate. Based on the testing conducted across multiple stages, it can be concluded that the Web-Based First In First Out (FIFO) Inventory Management Information System is suitable for use at CV Berkah Foam Furniture